Evaluation Of Digital Banking Application Adoption Based On The Technology Acceptance Model (Tam) - Nihayah, Naelun; Purnama, Nursya’bani (Publisher Cv. Inara, 2024)
In this digital era, digital banking has become an integral part of the banking sector. Users decisions to adopt and use digital banking services are significantly influenced by their perceptions and attitudes toward this technology. This research aims to analyze the factors that influence users' intention to use digital banking, utilizing the Technology Acceptance Model (TAM) as the theoretical framework. The study involves 100 respondents randomly selected through the method of random sampling. Data will be collected via an online questionnaire comprising TAM variables, including perceived usefulness and perceived ease of use. The data analysis will be conducted using the Partial Least Square Structural Equation Modeling (PLS-SEM) statistical method. The findings of this research are expected to provide a deeper insight into the factors affecting the adoption of digital banking and can serve as a guide for banks and financial service providers in enhancing the acceptance of digital banking technology among users.